MODEL PEMBELAJARAN WRITE AROUND MENGGUNAKAN MEDIA SOSIAL INSTAGRAM DALAM MENULIS KARANGAN BAHASA JEPANG (Studi Kasus Terhadap Kelompok Mahasiswa Semester IV DPBJ FPBS UPI Tahun Akademik 2019/2020) - Riski Destari, - (2020)
Penelitian ini merupakan penelitian yang mengaplikasikan model pembelajaran write around dikombinasikan dengan media sosial Instagram dalam menulis karangan bahasa Jepang yang diujicobakan kepada kelompok mahasiswa semester IV DPBJ FPBS UPI tahun akademik 2019/2020. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan, hasil dari pelaksanaan model pembelajaran, serta mendeskripsikan tanggapan responden terhadap model pembelajaran. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian deskriptif yang dikaji menggunakan studi kasus dan sampling. Data yang diperoleh merupakan data gabungan dari data kuantitatif dan data kualitatif. Penelitian dilakukan kepada 9 orang sampel mahasiswa yang dibagi ke dalam 3 kelompok. Desain model pembelajaran write around menggunakan Instagram yang direncanakan yaitu menulis kalimat secara bergantian yang hasilnya akan digabungkan menjadi hasil karangan, kemudian dikoreksi bersama-sama anggota kelompok. Hasil yang sudah dikoreksi diunggah bersama foto/video ke Instagram sebagai bentuk presentasi dari hasil karangan kelompok. Setelah itu, masing-masing kelompok saling memberikan komentar kepada kelompok lain. Pelaksanaan model pembelajaran dilakukan tiga kali perlakuan. Pada pelaksanaannya, sampel penelitian dapat mengembangkan tulisan dengan ungkapan perintah/pertanyaan serta foto/video sebagai stimulus untuk menulis. Dari hasil karangan, diketahui terdapat 22% mahasiswa dengan kemampuan menulis bahasa Jepang kategori sangat tinggi, 22% mahasiswa kategori tinggi, 56% mahasiswa dengan kategori menengah, 0% mahasiswa dengan kategori rendah dan sangat rendah. Dari hasil wawancara, diketahui bahwa model pembelajaran write around sangat bagus, mudah, menarik, dan menyenangkan. This study applied a write around learning model combined with social media Instagram in writing Japanese essay which tested on a group of 4th semester students of Japanese Language Education Departement, Faculty of Language and Literature, UPI, academic year of 2019/2020. The purpose of this research is to describe the implementation, results of the implementation, and describe the responses of the respondents about the learning model. This research used a descriptive research method using case studies and sampling. The obtained data is a combination of quantitative data and qualitative data. The study was conducted on 9 student samples divided into 3 groups. The design planned for the write around learning model using Instagram is to write sentences in turn and combine the result into an essay, and then correct it together with the group members. The corrected result uploaded with photos / videos to Instagram as a presentation of the group's results to be commented by the other groups. The study was conducted three times of treatments. In implementation, students can develop the essay with command expressions / questions and photos / videos as a stimulus for writing. From the essay results, it is known that there are 22% of students with very high category in Japanese writing ability, 22% of students in the high category, 56% of students in the middle category, 0% of students in the low and very low category. From the interview results, it is known that the write around learning model is very good, easy, interesting, and fun.This study applied a write around learning model combined with social media Instagram in writing Japanese essay which tested on a group of 4th semester students of Japanese Language Education Departement, Faculty of Language and Literature, UPI, academic year of 2019/2020. The purpose of this research is to describe the implementation, results of the implementation, and describe the responses of the respondents about the learning model. This research used a descriptive research method using case studies and sampling. The obtained data is a combination of quantitative data and qualitative data. The study was conducted on 9 student samples divided into 3 groups. The design planned for the write around learning model using Instagram is to write sentences in turn and combine the result into an essay, and then correct it together with the group members. The corrected result uploaded with photos / videos to Instagram as a presentation of the group's results to be commented by the other groups. The study was conducted three times of treatments. In implementation, students can develop the essay with command expressions / questions and photos / videos as a stimulus for writing. From the essay results, it is known that there are 22% of students with very high category in Japanese writing ability, 22% of students in the high category, 56% of students in the middle category, 0% of students in the low and very low category. From the interview results, it is known that the write around learning model is very good, easy, interesting, and fun.